Integrin crosstalk allows CD4+ T lymphocytes to continue migrating in the upstream direction after flow - Kim, Sarah Hyun Ji (Integr Biol (Camb), 2019)
In order to perform critical immune functions at sites of inflammation, circulatory T lymphocytes must be able to arrest, adhere, migrate and transmigrate on the endothelial surface. This progression of steps is coordinated by cellular adhesion molecules (CAMs), chemokines, and selectins presented on the endothelium. Two important interactions are between Lymphocyte Function-associated Antigen-1 (LFA-1) and Intracellular Adhesion Molecule-1 (ICAM-1) and also between Very Late Antigen-4 (VLA-4) and Vascular Cell Adhesion Molecule-1 (VCAM-1). Recent studies have shown that T lymphocytes and other cell types can migrate upstream (against the direction) of flow through the binding of LFA-1 to ICAM-1. Since upstream migration of T cells depends on a specific adhesive pathway, we hypothesized that mechanotransduction is critical to migration, and that signals might allow T-cells to remember their direction of migration after the flow is terminated. Cells on ICAM-1 surfaces migrate against the shear flow, but the upstream migration reverts to random migration after the flow is stopped. Cells on VCAM-1 migrate with the direction of flow. However, on surfaces that combine ICAM-1 and VCAM-1, cells crawl upstream at a shear rate of 800 s(−1) and continue migrating in the upstream direction for at least 30 minutes after the flow is terminated—we call this ‘migrational memory’. Post-flow upstream migration on VCAM-1/ICAM-1 surfaces is reversed upon the inhibition of PI3K, but conserved with cdc42 and Arp2/3 inhibitors. Using an antibody against VLA-4, we can block migrational memory on VCAM-1/ICAM-1 surfaces. Using a soluble ligand for VLA-4 (sVCAM-1), we can promote migrational memory on ICAM-1 surfaces. These results indicate that, while upstream migration under flow requires LFA-1 binding to immobilized ICAM-1, signaling from VLA-4 and PI3K activity is required for the migrational memory of CD4+ T cells. These results indicate that crosstalk between integrins potentiates the signal of upstream migration.